2012
DOI: 10.1148/radiol.12111605
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Fasting for Contrast-enhanced CT: Reconsideration

Abstract: There is little evidence that ingestion of clear inert fluid prior to contrast-enhanced CT is a cause of aspiration pneumonia; the length of fasting is variable in any country, being much longer in some hospitals than in others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…32 Similar results have been obtained for patients undergoing upper gastrointestinal endoscopy. 5,33 Findings from other studies suggest that fasting may not be necessary for computed tomography with intravenous contrast, 34 abdominal ultrasonography, 8 coronary intervention, 9 or conscious sedation. 35 Interestingly, a small study found that patients may be able to eat lunch even before an afternoon colonoscopy without compromising the quality of the study, as long as the bowels have been adequately prepared.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similar results have been obtained for patients undergoing upper gastrointestinal endoscopy. 5,33 Findings from other studies suggest that fasting may not be necessary for computed tomography with intravenous contrast, 34 abdominal ultrasonography, 8 coronary intervention, 9 or conscious sedation. 35 Interestingly, a small study found that patients may be able to eat lunch even before an afternoon colonoscopy without compromising the quality of the study, as long as the bowels have been adequately prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to scan emptiness of stomach and bowels were ensured. 21 Contrast material was given through a wide bore intravenous line placed in the antecubital fossa at the rate of 4 ml/sec and amount of 2 ml/kg contrast was injected. The patient was instructed to hold his/her breath for 10 seconds and scan was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…A standard protocol of CT scan was followed, 10,18 on a 16-slice MDCT scanner. 19 Contrast material was given at the rate of 4 ml/second and the patient was instructed to hold his/her breath for 10 seconds and scan was initiated. After a 10 to 15 seconds set delay of the of the contrast agent, acquisition of image data was started.…”
Section: Radiological Assessmentmentioning
confidence: 99%